MENINGKATKAN HASIL BELAJAR PESERTA DIDIK MELALUI MEDIA VIDEO PEMBELAJARAN PADA PEMBELAJARAN JARAK JAUH DI MASA PANDEMI COVID-19 - NORMA NORMA (SOCIAL : Jurnal Inovasi Pendidikan IPS, 2021)
The objectives of this literature review are; (1) To create real learning conditions for students during the Covid-19 Pandemic; (2) To find out the role of learning video media in the distance learning process; (3) To find out the effect between the use of learning video media on student learning outcomes during the Covid-19 Pandemic. This study uses quantitative research methods. The results of this study indicate that: (1) The implementation of distance learning processes during the Covid-19 Pandemic through learning videos. The results of the data showing the implementation of the learning process based on the student's attendance rate of 94% and the results of the pre-learning video media data, especially on the interest in social studies lessons by 42% after using the learning video media increased to 77%; (2) Learning video media can help teachers deliver material and create a learning situation that is not monotonous. The results of pre-learning video media data showing that learning video media can help teachers deliver material is 42% and after using learning video media it increases to 94%; (3) Learning video media can help students understand the subject matter and complete the tasks given by the teacher. The data from the pre-learning video media showing that students can answer questions through online learning is 19% after using the learning video media, increasing to 94%; (4) Appropriate and effective learning video media in increasing motivation and learning outcomes for students during the Covid-19 Pandemic. The results of pre-learning video media data showing the subject matter given to students online are very clear at 42% after using learning video media, increasing to 94%. ABSTRAKTujuan dari kajian pustaka ini adalah ; (1) Untuk menciptakan kondisi belajar yang nyata terhadap peserta didik di masa Pandemi Covid-19; (2) Untuk mengetahui peran media video pembelajaran dalam proses pembelajaran Jarak Jauh; (3) Untuk mengetahui pengaruh antara penggunaan media video pembelajaran terhadap hasil belajar peserta didik di masa Pandemi Covid-19. Kajian ini menggunakan metode penelitian kuantitatif. Hasil kajian ini menunjukkan bahwa : (1) Terselenggaranya proses belajar jarak jauh di masa Pandemi Covid-19 melalui video pembelajaran. Hasil data yang menunjukan terselenggaranya proses pembelajaran bedasarkan tingkat kehadiran peserta didik 94% dan hasil data pra media video pembelajaran khususnya pada minat pelajaran IPS sebesaar 42% setelah menggunakan media video pembelajaran meningkat menjadi 77%; (2) Media video pembelajaran dapat membantu guru menyampaikan materi dan menciptakan situasi pembelajaran yang tidak monoton. Hasil data pra media video pembelajaran yang menunjukan media video pembelajaran dapat membantu guru menyampaikan materi sebesar 42% dan setelah menggunakan media video pembelajaran meningkat menjadi 94%; (3) Media video pembelajaran dapat membantu peserta didik untuk memahami materi pelajaran dan menyelesaikan tugas yang di berikan guru. Data hasil pra media video pembelajaran yang menunjukan peserta didik dapat menjawab pertanyaan melalui pembelajaran daring sebesar 19% setelah menggunakan media video pembelajaran meningkat menjadi 94%; (4) Media video pembelajaran yang layak dan efektif dalam meningkatkan motivasi dan hasil belajar bagi peserta didik dimasa Pandemi Covid-19. Hasil data pra media video pembelajaran yang menunjukan materi pelajaran yang diberikan kepada peseta didik melalui daring sangat jelas sebesar 42% setelah menggunakan media video pembelajaran meningkat menjadi 94%.